2002
DOI: 10.1159/000067028
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Antiparkinsonian Treatment Reduction after Subthalamic Nucleus Stimulation

Abstract: The objective of this work was to precisely analyse the reduction of the antiparkinsonian treatment in 18 consecutive patients with Parkinson’s disease (PD) operated on for bilateral subthalamic nucleus (STN) stimulation, first after 1 month of follow-up, then at 1 year postoperatively. Trihexyphenidyle, selegiline, entacapone, apomorphine and lisuride could be withdrawn shortly after starting STN electrical stimulation. The levodopa mean daily dose was reduced by 57% at 1 month after surgery and remained stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
12
0
4
Order By: Relevance
“…This reduction was usually achieved in the first 6 months after the surgery, the treatment remaining stable thereafter [38]. The magnitude of antiparkinsonian drugs reduction reported in the literature is variable and comprised between 35% and 63% [17, 19, 30-32, 34-32, 39, 40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction was usually achieved in the first 6 months after the surgery, the treatment remaining stable thereafter [38]. The magnitude of antiparkinsonian drugs reduction reported in the literature is variable and comprised between 35% and 63% [17, 19, 30-32, 34-32, 39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Three to five days later a subcutaneous programmable pulse generator (Itrell II or Kinetra, Medtronic, Minneapolis, Minn) was implanted under general anaesthesia and connected to the electrodes. The adjustment of the stimulation parameters and of the medications was done progressively as previously reported [38].…”
Section: Materials and Methods J Patientsmentioning
confidence: 99%
“…We evaluated the anatomical localization of the chronic active contacts as well as the DB and VB of the STN in 28 patients (56 electrodes) for whom complete clinical, neurophysiological and imaging data were available. Criteria for admission to the surgical program have been described elsewhere [75]. All patients suffered advanced intractable idiopathic Parkinson's disease and preserved levodopa effectiveness, but with severe motor fluctuations, prolonged off-periods and dyskinesias.…”
Section: Patients and Methods J Patientsmentioning
confidence: 99%
“…The most efficient contact was defined as that which resulted in (i) the best clinical improvement at the lowest stimulation voltage, and (ii) the largest therapeutic range before induction of side effects. Then, progressive adjustment of the parameters of stimulation was conducted in parallel with a drug reduction as previously described [75]. The parameters of stimulation were at 6 months: voltage, 3.08 ± 0.43 V; pulse width, 67.22 ± 12.94 lsec; frequency, 153.61 ± 19.67 Hz.…”
Section: Electrode Placementmentioning
confidence: 99%
“…Objective To determine in Parkinson's disease (PD) patients using positron emission tomography (PET) and [ s Key words Parkinson's disease · subthalamic stimulation · dopamine · raclopride · PET obtained in rats suggest that dopamine (DA) or its metabolites could be affected by such a stimulation [15,20,21,22]. Interestingly, it has also been reported that DAergic medication may be reduced by almost 50 % in PD patients treated by STN stimulation [29,32]. This observation strongly suggests that HFS-STN could affect striatal DA transmission.…”
Section: Introductionmentioning
confidence: 99%